1986
DOI: 10.1254/jjp.40.505
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Immune Responses I. Suppression of T Cell Function in Restraint-Stressed Mice

Abstract: Abstract-Effectsof restraint stress on humoral immune responses were investi gated in mice. Mice were restrained for 12 hours per day at nighttime and released at daytime for 2 consecutive days, either before or after sheep red blood cell (SRBC) immunization.The antibody response to SRBC was markedly suppressed in mice that were restrained before antigen injection.In contrast, the response was not significantly affected when the stress was loaded after immunization.Oral admin istration of 10 mg/kg diazepam pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It was reported that repeated stress-induced reduction of immune functions affects not only NK cells but also the functions of antitumor T cells [27] and differentiation of antibody-forming cells [28]. Thus, medication with various immunoactivators [29] and Chinese herbal remedies [30,31] has been investigated as a method of improving changes in immune functions in stressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that repeated stress-induced reduction of immune functions affects not only NK cells but also the functions of antitumor T cells [27] and differentiation of antibody-forming cells [28]. Thus, medication with various immunoactivators [29] and Chinese herbal remedies [30,31] has been investigated as a method of improving changes in immune functions in stressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated for several quantitative and qualitative aspects of immune func tion, including nonspecific innate immune parameters [15][16][17][18][19][20][21], and specific T and B lymphocyte functions, including those against infectious and tumor antigens [22][23][24][25][26][27][28][29][30][31][32][33], How ever, there is a lack of consensus as to which types of stres sors are likely to promote specific types of alterations in a particular parameter of immune function. For example, whereas some researchers have found stressor-induced sup pression of antibody production in rats or mice [34][35][36], others find an enhancement in antibody formation [37,38]. Explanations for these anomalies may be sought in varia bles such as the type and duration of the particular stressor being used, characteristics of the specific antigen, the spe cies of animal tested, strain and sex of the experimental sub ject.…”
Section: Modulation Of the Immune Function By Stressmentioning
confidence: 99%
“…Accepted January 6,1986 Abstract-The influences of restraint stress on the functions of T cells, B cells and adherent cells in antibody responses were investigated. Antibody response against sheep red blood cells (SRBC), a T cell-dependent antigen, in cultured splenocytes from restrained mice was reduced to about 40-50% of that from the control mice.…”
Section: Tamatsukurimentioning
confidence: 99%
“…In a previous paper, we investigated the effects of restraint stress on immune responses in mice and found that restraint stress caused sup pression of the antibody responses to T cell dependent (TD) antigens, but did not suppress the responses against T cell independent (TI) antigens (6). For the mechanisms of the diverse effects of restraint stress, we propose the following three hypo theses: (1) B cell populations that respond to TI antigens are essentially resistant against stress procedures.…”
Section: Tamatsukurimentioning
confidence: 99%